2015
DOI: 10.3329/icpj.v4i7.23590
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of UV-spectrophotometric methods for quantitative estimation of Prothionamide in pure and pharmaceutical dosage forms

Abstract: UV Spectrophotometric method was developed and validated for the quantitative determination of Prothionamide in bulk drug and in pharmaceutical formulations. Prothionamide shows the maximum absorbance at 288 nm in phosphate buffer (pH 7.4). Prothionamide follows Beer’s law in the concentration range of 4-20 µg/ml (r2 = 0.999). The detection limit (DL) and quantitation limit (QL) were 0.406 and 1.229 µg/ml respectively. Accuracy and precision were found to be satisfactory. The developed methods were validated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Percentage Drug Entrapment (PDE) of PTH in nanoparticles was determined by separating the nanoparticles from the aqueous medium by ultracentrifugation at 31150g for 30 min. The amount of free PTH in the supernatant was measured by UV-Spectrophotometery at 288nm [ 15 ]. Other evaluation parameters were calculated as reported previously [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Percentage Drug Entrapment (PDE) of PTH in nanoparticles was determined by separating the nanoparticles from the aqueous medium by ultracentrifugation at 31150g for 30 min. The amount of free PTH in the supernatant was measured by UV-Spectrophotometery at 288nm [ 15 ]. Other evaluation parameters were calculated as reported previously [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, un-entrapped PTH in the supernatant was estimated by UV-spectrophotometric method as reported previously [15]. Entrapped drug was calculated by subtracting un-entrapped drug from total drug.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…These vials were kept in stability chamber and maintained at 25±2°C & 60±5% RH. The nanoparticles were analyzed for the period of 6 month [15,21,22]. Zeta size, zeta potential, PDI, drug entrapment and drug release were carried out to check the stability of dry powder inhaler of PTH nanoparticles.…”
Section: Accelerated Stability Studymentioning
confidence: 99%
“…8 Considering the above mentioned side effects, researchers have developed various analytical tools for the determination and quantication of ETO from various formulations and even real samples. [9][10][11][12][13][14][15] For example, Sujitkumar et al reported a UV-Vis spectrophotometric method for ETO estimation from bulk and tablets. 10 Madni et al gave an account of an HPLC method for the determination of ETO from serum.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] For example, Sujitkumar et al reported a UV-Vis spectrophotometric method for ETO estimation from bulk and tablets. 10 Madni et al gave an account of an HPLC method for the determination of ETO from serum. 11 Moreover, the spectrometric estimation of ETO was carried out using Folin-Ciocalteu reagent with iron(III)-ferricyanide as the chromogenic agent complexing with ETO.…”
Section: Introductionmentioning
confidence: 99%